Light‐Responsive (Supra)Molecular Architectures: Recent Advances. Issue 16 (17th May 2019) - Baroncini, Massimo; Groppi, Jessica; Corra, Stefano; Silvi, Serena; Credi, Alberto
Abstract: The development and investigation of (supra)molecular‐based architectures characterized by light‐activated functionalities is a highly relevant topic of chemical research. The interest on photo‐controlled systems arises not only from their potential applications in different fields of technology but also from their scientific significance related to the understanding of light–matter interactions at the nanoscale. Indeed, light is a peculiar and unique tool as it can be conveniently applied to supply the energy required to affect and operate a system and, at the same time, to probe its state and investigate its transformations. Some basic aspects of light‐induced processes in (supra)molecular architectures are discussed here in the frame of their use to implement novel functionalities in nanostructured systems and materials. In this perspective, a few recent examples from our own work will be illustrated which are meant to provide an overview of the current directions in this highly cross‐disciplinary field of research. Abstract : Photoactive materials are actively researched as a playground for understanding light–matter interaction and developing novel technological applications. Light radiation is a unique tool to supply energy to a chemical system, probe its state, and trigger and investigate its transformations. The basic aspects of azobenzene photochromes are discussed in the frame of their exploitation to develop photoresponsive nanostructured materials.